Climate & Food Security Monitoring Bulletin Maha Season 2019 - 2020 - International Water Management Institute; World Food Programme (2020)
A successful Maha Season 2019-2020 means paddy production is estimated to be sufficient to meet domestic demand until September 2020. Floods, mainly along the East and North coast, caused an estimated production loss of 57,065 Mt. This however, should not have an impact on short- to medium-term food security. Limitation of vegetables and onions were observed in early 2020.